A long-life magnesium oxide crucible, a preparation method and application thereof
Patent Information
- Application Number
- CN202611140140.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-30
AI Technical Summary
[0005]但该单层结构坩埚存在明显应用局限性,无法适配高铝钛含量的高温合金
(1)本发明采用上部抗热震层、下部抗侵蚀层的双层结构,两层材料热膨胀系数不同,能够有效抑制坩埚微裂纹扩展;搭配石墨芯梯度功率烧结工艺,配合采用纯铁和纯镍进行洗炉处理,使抗侵蚀层形成0.5-1.0mm的致密烧结壳层,可有效阻隔高流动性合金熔体渗透,彻底解决传统单层坩埚在熔炼高铝钛高温合金时易渗漏、蚀损的问题,提高了氧化镁坩埚的纯净度。
Smart Images

Figure CN122647246B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a crucible, specifically to a long-life magnesium oxide crucible, its preparation method, and its application. Background Technology
[0002] In the field of casting high-temperature alloy production, vacuum induction furnaces are the mainstream melting equipment, capable of precisely controlling the temperature, chemical composition, and vacuum level of molten metal, and are widely used. Magnesium oxide crucibles, as the core furnace lining component of vacuum induction furnaces, are in direct contact with the high-temperature molten metal. During the melting process, they are continuously subjected to molten metal erosion and chemical corrosion. Furthermore, cleaning inclusions from the inner wall of the crucible can easily cause wall damage, leading to problems such as cracks, localized corrosion, and surface peeling. Therefore, developing long-life magnesium oxide crucibles with high density, high structural strength, erosion resistance, and thermal shock resistance is a key research focus in the industry.
[0003] Currently, the commonly used furnace linings for vacuum induction furnaces are mainly made of three types of crucibles: calcium oxide, magnesium oxide, and aluminum oxide. The forming process is divided into ramming forming and isostatic pressing forming. Crucibles for large melting furnaces with a capacity of 200 kg or more are mostly made using the ramming forming process, while crucibles for small melting furnaces with a capacity of less than 200 kg are mainly made using isostatic pressing forming.
[0004] Chinese patent CN112321282A discloses a high-strength magnesium oxide crucible and its preparation method. It employs a single-layer integral structure, manufactured through batching and mixing, pre-calcination and granulation, secondary mixing and compaction, and high-temperature baking, forming a sintered layer of a certain thickness. This type of single-layer magnesium oxide crucible performs reasonably well when smelting iron-based and conventional nickel-based high-temperature alloys. These alloys have relatively high density and weak melt fluidity; even if minor cracks appear in the sintered layer of the crucible, they will not quickly affect the overall performance. After simple repairs, it can be put back into production, basically meeting the needs of conventional operating conditions.
[0005] However, this single-layer crucible structure has significant application limitations and cannot be adapted to high-temperature alloys with high aluminum and titanium content. Taking K424, K417, and K417G alloys in the HB7763-2020 standard as examples, these alloys have a total aluminum and titanium content of ≥6.0wt% and excellent melt fluidity. Once a tiny crack appears on the inner wall of the crucible, the high-temperature molten metal will quickly penetrate along the crack, significantly shortening the crucible's service life and causing alloy melt contamination, thus reducing the purity of the finished product.
[0006] Meanwhile, when traditional single-layer magnesium oxide crucibles are used in large vacuum melting furnaces of 500 kg and above, their overall service life is relatively short. The service life of conventional single-layer crucibles used in ton-class melting furnaces is generally only about 30 heats. During long-term use, large-area cracks easily develop in the crucible walls, requiring frequent shutdowns for repairs. This not only severely reduces production efficiency, but also causes the detached crucible material to continuously contaminate the molten metal.
[0007] In light of the actual production conditions of high-alumina titanium high-temperature alloys and large vacuum induction melting furnaces, the industry urgently needs a magnesium oxide crucible that can effectively block the penetration of alloy melt, inhibit crack propagation, and has better overall performance and service life. Summary of the Invention
[0008] To address the shortcomings of existing technologies, the present invention aims to provide a long-life magnesium oxide crucible, its preparation method, and its application. Employing a double-layered composite structure with differentiated refractory material systems, and sintered, it effectively blocks the penetration of highly fluid alloy melts along microcracks and inhibits further crack propagation. This significantly improves the crucible's resistance to erosion and thermal shock, as well as its overall service life, thereby meeting the long-term stable use requirements of high-aluminum-titanium content high-temperature alloys and large vacuum induction melting furnaces.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: The method for preparing the high-life magnesium oxide crucible includes the following steps: (1) Batching steps: Prepare the first mixed raw material for the thermal shock resistant layer in the upper part of the crucible and the second mixed raw material for the erosion resistant layer in the lower part of the crucible. Add 3-5% water to the first mixed raw material and mix evenly. Do not add water to the second mixed raw material. The mass percentage of MgO in the second mixed raw material is 75.0-77.0%. (2) Compaction molding step: The first and second mixed raw materials are arranged in upper and lower layers and tamped or vibrated to form a crucible blank with a double-layer composite structure; the volume of the thermal shock resistant layer accounts for 15-20% of the total volume of the crucible blank, and the volume of the erosion resistant layer accounts for 80-85% of the total volume of the crucible blank; (3) Sintering step: The graphite core is placed into the prepared crucible blank and sintered. After sintering, the graphite core is removed and the furnace is cleaned with pure iron and pure nickel respectively to obtain a high-life magnesium oxide crucible. The sintering process is as follows: 195-205kW holding time for 118-122 minutes, 295-305kW holding time for 58-62 minutes, 345-355kW holding time for 58-62 minutes, 375-385kW holding time for 58-62 minutes, 395-405kW holding time for 28-32 minutes, 445-455kW holding time for 28-32 minutes, and 495-505kW holding time for 28-32 minutes.
[0010] Preferably, the first mixed raw material comprises the following chemical components by mass percentage: MgO: 53.0-54.0%, Al2O3: 34.0-35.0%, SiO2: 7.0-8.0%, TiO2: 1.0-1.5%, CaO: 1.0-1.5%, Fe2O3: 0.4-0.6%, MgCl2: 0.5-1.0%, Na2O·nSiO2: 0.5-1.0%.
[0011] The chemical composition of the first mixture is explained as follows: It contains high levels of Al2O3 and SiO2, belongs to a high-alumina / silicate bonding system, and is mainly used as a sintering aid and binder phase.
[0012] MgO: As a refractory matrix, it ensures the crucible's high refractoriness (melting point 2800℃) and resistance to alkaline slag erosion.
[0013] Al2O3: contributes to spinel formation and crucible densification during sintering.
[0014] SiO2 reacts with MgO at high temperatures to form a low-melting-point phase, forsterite (Mg2SiO4), and a glassy phase, which helps to lower the sintering temperature. Simultaneously, the glassy phase forms a ceramic bond upon cooling, enhancing the crucible's room-temperature strength.
[0015] MgCl2: After melting and hydrating at low temperatures (<500℃), it acts as a temporary binder, maintaining the strength of the green body and facilitating molding.
[0016] Na2O·nSiO2: Commonly known as water glass / sodium silicate, it is used as a high-temperature binder and rheology modifier to increase the fluidity of the slurry and improve the density of the green body during molding.
[0017] Preferably, the second mixed raw material comprises the following chemical components in weight percentage: MgO: 75.0-77.0%, Al2O3: 21.0-23.0%, SiO2: 0.4-0.6%, CaO: 0.5-1.0%, MgCl2: 0.4-0.6%.
[0018] The chemical composition of the second mixture is explained below: It is mainly composed of MgO and low in Al2O3, and is the main raw material for the formation of magnesium aluminum spinel (MgAl2O4).
[0019] MgO: As the core raw material, it reacts with Al2O3 at high temperature to form magnesium aluminum spinel (MgAl2O4). This phase has excellent thermal shock stability and corrosion resistance, and is the main source of crucible strength.
[0020] Al2O3: contributes to spinel formation and crucible densification during sintering.
[0021] SiO2: Reduces the formation of the glass phase and improves high-temperature strength.
[0022] MgCl2: It decomposes / volatiles at high temperatures, leaving no harmful impurities; at the same time, the released gas channels can promote degassing in the early stage of sintering and reduce the risk of cracking of the green body.
[0023] The preferred process for furnace cleaning using pure iron is as follows: hold at 95-105kW for 18-22 minutes, hold at 155-165kW for 18-22 minutes, hold at 215-225kW for 8-12 minutes, raise the temperature to 1680-1700℃ at 445-455kW, then adjust the power to 155-165kW and hold for 28-32 minutes, then turn off the power and cool down to 1595-1605℃, then adjust the power to 295-305kW and raise the temperature to 1645-1655℃ for pouring (i.e., pouring out the molten iron).
[0024] The preferred process for furnace cleaning using pure nickel is as follows: hold at 95-105kW for 18-22 minutes, hold at 155-165kW for 18-22 minutes, hold at 215-225kW for 8-12 minutes, raise the temperature to 1590-1610℃ at 445-455kW, then adjust the power to 155-165kW and hold for 28-32 minutes, then turn off the power and cool down to 1565-1575℃, then adjust the power to 295-305kW and raise the temperature to 1585-1595℃ for pouring (i.e., pouring out the molten nickel).
[0025] Preferably, the sintering product of the thermal shock resistant layer includes magnesium oxide, aluminum oxide, titanium oxide and iron oxide; the sintering product of the corrosion resistant layer includes magnesium aluminum spinel, magnesium oxide and aluminum oxide; the corrosion resistant layer has a dense sintered shell layer with a thickness of 0.5-1.0 mm.
[0026] After the graphite core is sintered, a dense sintered shell layer is formed on the inner wall of the lower part of the crucible. Then, the furnace is cleaned with pure iron and pure nickel to remove inclusions inside the crucible, improve the service life of the crucible, and reduce the introduction of impurity elements into the preparation of high-performance high-temperature alloy materials.
[0027] The relationship between the thickness of the dense sintered shell and the service life of the crucible is as follows: if the dense sintered shell is too thin, it is easily damaged during subsequent repairs, causing irreversible damage and reducing the crucible's service life; if the dense sintered shell is too thick, the magnesium oxide crucible will experience significant thermal expansion and contraction after use, leading to more cracks. Only when the thickness of the dense sintered shell is maintained at an appropriate level can the crucible be less susceptible to damage during repairs, while also reducing the stress caused by thermal expansion and contraction, ultimately improving the crucible's service life.
[0028] Magnesium aluminum spinel (MgAl2O4) plays a crucial role in strengthening the framework, resisting thermal shock, and resisting corrosion in magnesium oxide crucibles. It is generated in situ through the high-temperature reaction of MgO and Al2O3, or directly introduced as a pre-synthesized raw material. On one hand, the mismatch in thermal expansion coefficients between spinel and periclase leads to the formation of numerous microcracks within the material. These microcracks act as "buffer zones," effectively absorbing and dispersing thermal shock energy, causing crack deflection, and preventing crack propagation and penetration, thus significantly improving the crucible's resistance to rapid heating and cooling. On the other hand, spinel has a high melting point of 2135℃, stable chemical properties, and excellent resistance to alkaline slag and molten metal. It can form a dense reaction layer to block slag penetration, while the uniformly distributed spinel phase can pin the periclase grain boundaries, inhibiting abnormal grain growth, maintaining microstructural stability, and promoting material densification.
[0029] The high-life magnesium oxide crucible of the present invention is prepared by the above-described method for preparing a high-life magnesium oxide crucible.
[0030] The application of the high-life magnesium oxide crucible described in this invention is for use in vacuum melting furnaces of 500kg and above, for casting high-temperature alloys containing a high aluminum and titanium content, wherein the high aluminum and titanium content is: aluminum + titanium ≥ 6.0 wt%. It includes K447A, K424, K417, and K417G alloys.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention adopts a double-layer structure with an upper thermal shock-resistant layer and a lower anti-corrosion layer. The two layers have different thermal expansion coefficients, which can effectively suppress the propagation of microcracks in the crucible. Combined with the graphite core gradient power sintering process and the use of pure iron and pure nickel for furnace cleaning treatment, the anti-corrosion layer forms a dense sintered shell layer of 0.5-1.0 mm, which can effectively block the penetration of high-fluidity alloy melt, completely solve the problem of easy leakage and corrosion of traditional single-layer crucibles when smelting high-alumina titanium high-temperature alloys, and improve the purity of magnesium oxide crucibles.
[0032] (2) The present invention adopts a double-layer structure to realize functional partition design. The thermal shock resistant layer can withstand the sudden temperature change during the melting process and avoid thermal shock cracking of the upper part of the crucible. The anti-erosion layer has excellent resistance to molten liquid erosion and chemical erosion. The two layers complement each other, significantly improving the overall performance and service life of the crucible and greatly reducing the frequency of crucible repair and replacement.
[0033] (3) The preparation process of this invention is simple and controllable. The layered ramming and sintering process makes the two-layer structure tightly bonded and not easy to delaminate, resulting in strong product stability. It is suitable for large vacuum melting furnaces of 500kg and above and high-temperature alloy melting conditions with a total aluminum + titanium content of ≥6.0%. It can improve production continuity and efficiency, and avoid refractory material impurities from mixing into the melt, ensuring the purity of the alloy product. It has good prospects for industrial application. Attached Figure Description
[0034] Figure 1 This is an X-ray diffraction (XRD) phase analysis diagram of the anti-erosion layer (lower layer) prepared in Example 1; Figure 2 This is an X-ray diffraction (XRD) phase analysis diagram of the thermal shock resistant layer (upper layer) prepared in Example 1. Detailed Implementation
[0035] The present invention will be further described below with reference to the embodiments.
[0036] Unless otherwise specified, all raw materials used in the examples were commercially available.
[0037] In both the examples and comparative examples, a 500kg vacuum induction furnace was used for the experiments.
[0038] Example 1 The preparation method of the high-life magnesium oxide crucible comprises the following steps: (1) Raw material preparation: Composition of the thermal shock resistant layer (upper layer) (wt%): MgO: 53.5%, Al2O3: 34.5%, SiO2: 7.5%, TiO2: 1.2%, CaO: 1.2%, Fe2O3: 0.5%, MgCl2: 0.8%, Na2O·nSiO2: 0.8%. Add 4% (by weight of the total raw materials of the thermal shock resistant layer (upper layer) of clean water.
[0039] Composition of the erosion-resistant layer (lower layer) (wt%): MgO: 76.2%, Al2O3: 22.0%, SiO2: 0.5%, CaO: 0.8%, MgCl2: 0.5%.
[0040] (2) Compacting and molding: Using a 500kg vacuum induction furnace crucible mold, first add 80% of the anti-erosion layer mixture, and tamp until the lower anti-erosion layer is formed; then add 20% of the thermal shock resistant layer mixture, and continue tamping until the whole is dense to obtain the crucible blank.
[0041] (3) Graphite core sintering: Place the graphite core in the center of the blank and sinter according to the following power-time curves: 200kW for 120min, 300kW for 60min, 350kW for 60min, 380kW for 60min, 400kW for 30min, 450kW for 30min, and 500kW for 30min. Cool naturally to room temperature and remove the graphite core.
[0042] The furnace is cleaned using pure iron, and the specific process is as follows: hold at 100kW for 20 minutes, hold at 160kW for 20 minutes, hold at 220kW for 10 minutes, raise the temperature to 1690℃ at 450kW, then adjust the power to 160kW and hold for 30 minutes, then turn off the power and cool down to 1600℃, then adjust the power to 300kW and raise the temperature to 1650℃ for casting.
[0043] The furnace is cleaned using pure nickel, and the specific process is as follows: hold at 100kW for 20 minutes, hold at 160kW for 20 minutes, hold at 220kW for 10 minutes, raise the temperature to 1600℃ at 450kW, then adjust the power to 160kW and hold for 30 minutes, then turn off the power and cool down to 1570℃, then adjust the power to 300kW and raise the temperature to 1590℃ for casting.
[0044] (4) Performance verification: The prepared crucible was used to melt K447A alloy (Al+Ti≈6.4%) in a 500kg vacuum induction furnace. The service life of the crucible was 85 heats (the failure criterion was the appearance of obvious chemical erosion pits or visible through-cracks on the inner wall of the crucible). Cross-sectional inspection showed that a dense sintered shell layer with a thickness of 0.8mm was formed on the inner wall of the anti-erosion layer, and the main phase was magnesium aluminum spinel; no through-cracks were found on the cross-section of the thermal shock resistant layer.
[0045] The prepared crucible was used in a 500kg vacuum induction furnace to melt K424 alloy (Al+Ti≈9.35%). The crucible had a service life of 81 heats.
[0046] The X-ray diffraction (XRD) phase analysis pattern of the erosion-resistant layer (lower layer) prepared in Example 1 is shown in Figure 1. Figure 1 The X-ray diffraction (XRD) phase analysis pattern of the thermal shock resistant layer (upper layer) prepared in Example 1 is shown in the figure. Figure 2 It can be seen that the sintering products of the erosion-resistant layer include magnesium aluminum spinel, magnesium oxide, and aluminum oxide; the sintering products of the thermal shock-resistant layer include magnesium oxide, aluminum oxide, titanium oxide, and iron oxide.
[0047] Example 2 The preparation method of the high-life magnesium oxide crucible comprises the following steps: (1) Raw material preparation: Composition of the thermal shock resistant layer (upper layer) (wt%): MgO: 53.0%, Al2O3: 34.9%, SiO2: 7.0%, TiO2: 1.5%, CaO: 1.5%, Fe2O3: 0.6%, MgCl2: 1.0%, Na2O·nSiO2: 0.5%. Add 3% (by weight of the total mass of the thermal shock resistant layer (upper layer) raw materials, of clean water.
[0048] Composition of the anti-erosion layer (lower layer) (wt%): MgO: 75.0%, Al2O3: 23.0%, SiO2: 0.6%, CaO: 1.0%, MgCl2: 0.4%.
[0049] (2) Compacting and molding: Using a 500kg vacuum induction furnace crucible mold, first add 80% of the anti-erosion layer mixture, and tamp until the lower anti-erosion layer is formed; then add 20% of the thermal shock resistant layer mixture, and continue tamping until the whole is dense to obtain the crucible blank.
[0050] (3) Graphite core sintering: Place the graphite core in the center of the blank and sinter according to the following power-time curves: 195kW for 118min, 295kW for 58min, 345kW for 58min, 375kW for 58min, 395kW for 28min, 445kW for 28min, and 495kW for 28min. Cool naturally to room temperature and remove the graphite core.
[0051] The furnace is cleaned using pure iron, and the specific process is as follows: hold at 95kW for 18 minutes, hold at 155kW for 18 minutes, hold at 215kW for 8 minutes, raise the temperature to 1680℃ at 445kW, then adjust the power to 155kW and hold for 28 minutes, then stop the power and cool down to 1595℃, then adjust the power to 295kW and raise the temperature to 1645℃ for casting.
[0052] The furnace is cleaned using pure nickel, and the specific process is as follows: hold at 95kW for 18 minutes, hold at 155kW for 18 minutes, hold at 215kW for 8 minutes, raise the temperature to 1590℃ at 445kW, then adjust the power to 155kW and hold for 28 minutes, then stop the power and cool down to 1565℃, then adjust the power to 295kW and raise the temperature to 1585℃ for casting.
[0053] (4) Performance verification: K447A alloy: crucible life 78 heats; dense shell thickness 0.7mm; failure mode is uniform slow erosion, without spalling.
[0054] K424 alloy: crucible life 74 furnaces; failure mode is uniform slow erosion, without spalling.
[0055] Example 3 The preparation method of the high-life magnesium oxide crucible comprises the following steps: (1) Raw material preparation: Composition of the thermal shock resistant layer (upper layer) (wt%): MgO: 54.0%, Al2O3: 34.1%, SiO2: 8.0%, TiO2: 1.0%, CaO: 1.0%, Fe2O3: 0.4%, MgCl2: 0.5%, Na2O·nSiO2: 1.0%. Add 5% (by weight of the total mass of the thermal shock resistant layer (upper layer) raw materials, clean water.
[0056] Composition of the erosion-resistant layer (lower layer) (wt%): MgO: 77.0%, Al2O3: 21.5%, SiO2: 0.4%, CaO: 0.5%, MgCl2: 0.6%.
[0057] (2) Compacting and molding: Using a 500kg vacuum induction furnace crucible mold, first add 85% of the anti-erosion layer mixture to the total volume and tamp until the lower anti-erosion layer is formed; then add 15% of the thermal shock resistant layer mixture to the total volume and continue tamping until the whole is dense to obtain the crucible blank.
[0058] (3) Graphite core sintering: Place the graphite core in the center of the blank and sinter according to the following power-time curves: 205kW for 122min, 305kW for 62min, 355kW for 62min, 385kW for 62min, 405kW for 32min, 455kW for 32min, and 505kW for 32min. Cool naturally to room temperature and remove the graphite core.
[0059] The furnace is cleaned using pure iron, and the specific process is as follows: hold at 105kW for 22 minutes, hold at 165kW for 22 minutes, hold at 225kW for 12 minutes, raise the temperature to 1700℃ at 455kW, then adjust the power to 165kW and hold for 32 minutes, then stop the power and cool down to 1605℃, then adjust the power to 305kW and raise the temperature to 1655℃ for casting.
[0060] The furnace was cleaned using pure nickel, and the specific process was as follows: 105kW holding for 22 minutes, 165kW holding for 22 minutes, 225kW holding for 12 minutes, 455kW heating to 1610℃, then adjusting the power to 165kW holding for 32 minutes, power off cooling to 1575℃, then adjusting the power to 305kW, heating to 1595℃, and then casting.
[0061] (4) Performance verification: K447A alloy: crucible life 83 heats; dense shell thickness 0.9mm; failure mode is uniform slow erosion, without spalling.
[0062] K424 alloy: crucible life 80 heats; failure mode is uniform slow erosion, without spalling.
[0063] Comparative Example 1 The preparation method of the magnesium oxide crucible comprises the following steps: (1) Raw material preparation: (wt%): MgO: 76.2%, Al2O3: 22.0%, SiO2: 0.5%, CaO: 0.8%, MgCl2: 0.5%.
[0064] (2) Preparation process: The whole is compacted in one step, the same as the preparation process in Example 1.
[0065] (3) Performance verification: K447A alloy: The crucible life is only 35 heats. The failure mode is circumferential cracking caused by thermal shock at the upper opening, which extends rapidly downwards and is infiltrated by molten metal, resulting in premature scrapping.
[0066] K424 alloy: The crucible has a lifespan of only 33 heats. The failure mode is circumferential cracking caused by thermal shock at the upper opening, which extends rapidly downwards and is infiltrated by molten metal, resulting in premature scrapping.
[0067] Single-layer crucibles made from a single anti-corrosion layer material have poor thermal shock resistance. The upper part of the crucible is prone to cracking due to thermal shock, resulting in premature failure and a significantly shortened service life.
[0068] Comparative Example 2 The preparation method of the magnesium oxide crucible comprises the following steps: (1) Raw material preparation: the volume ratio of the thermal shock resistant layer is 50%, the volume ratio of the anti-corrosion layer is 50%, and the composition is the same as in Example 1.
[0069] (2) The preparation process is the same as in Example 1, except for the proportion of materials used.
[0070] (3) Performance verification: K447A alloy: lifespan 39 heats, failure mode is premature depletion of the erosion layer, molten metal directly erodes the thermal shock resistant layer, leading to structural instability.
[0071] K424 alloy: lifespan 41 heats, failure mode is premature depletion of the erosion layer, molten metal directly erodes the thermal shock resistant layer, leading to structural instability.
[0072] An excessively high proportion of thermal shock resistant layer leads to insufficient effective thickness of anti-corrosion layer, causing the alloy melt to rapidly erode the crucible body during the smelting process, resulting in premature crucible failure.
[0073] Comparative Example 3 The preparation method of the magnesium oxide crucible comprises the following steps: (1) Raw material preparation: Anti-erosion layer composition (wt%): MgO: 68.0%, Al2O3: 30.0%, SiO2: 1.0%, CaO: 0.5%, MgCl2: 0.5%; The thermal shock resistant layer is the same as in Example 1, with a volume ratio of 25 / 75 (upper layer / lower layer).
[0074] (2) The preparation process is the same as in Example 1.
[0075] (3) Performance verification: K447A alloy: lifespan is only 30 heats, failure mode is severe chemical corrosion, crucible wall thickness reduction exceeds 50%.
[0076] K424 alloy: lifespan is only 28 heats, failure mode is severe chemical corrosion, crucible wall thickness reduction exceeds 52%.
[0077] The insufficient magnesium oxide content in the anti-corrosion layer significantly reduces the crucible's resistance to chemical corrosion and erosion, resulting in noticeable thinning of the crucible wall and a substantial reduction in its service life.
[0078] Comparative Example 4 The preparation method of the magnesium oxide crucible comprises the following steps: (1) Raw material preparation: The ingredients of Example 1 were used; (2) Preparation process: The difference from Example 1 is that in step (3), only graphite core sintering is performed, and furnace cleaning is not performed.
[0079] (3) Performance verification: K447A alloy: The crucible life is only 20 heats. The failure mode is that the inner wall is loose and there is no dense shell. The strength is seriously insufficient and the whole spalling occurs.
[0080] K424 alloy: The crucible life is only 19 furnaces. The failure mode is that the inner wall is loose and there is no dense shell. The strength is seriously insufficient and the whole spalling occurs.
[0081] Without the furnace cleaning process using pure iron and pure nickel, the graphite and impurities remaining on the inner wall of the crucible react with the molten alloy in the early stages of smelting, damaging the structural integrity of the inner wall of the crucible and resulting in a significant reduction in its service life.
[0082] The performance verification results of the crucibles in the examples and comparative examples are summarized in Table 1.
[0083] Table 1 Performance verification results of the crucibles in the examples and comparative examples
[0084] As shown in Table 1, the double-layer structure of this invention, combined with gradient power sintering of the graphite core and furnace cleaning treatment, achieves a crucible life of 78-85 heats with K447A as an example, significantly better than the single-layer structure (35 heats) and the layer ratio imbalance (39 heats). When the MgO content of the anti-corrosion layer is lower than the lower limit of this invention, the lifespan drops sharply to 30 heats, proving that 75.0-77.0% is the necessary range. Without furnace cleaning treatment, the lifespan is only 20 heats and erosion pits appear on the inner wall, indicating that the furnace cleaning process is indispensable. The comparative examples all showed thermal shock penetration cracking or severe erosion, while the examples showed slow and uniform wear, indicating a fundamental change in the failure mechanism. This invention, through the synergistic effect of double-layer functional zoning and gradient sintering, increases the lifespan of high-alumina titanium alloy crucibles by approximately 2.5 times compared to existing single-layer structures.
[0085] Taking K424 as an example: the crucible life reaches 74-81 heats, significantly better than the single-layer structure (33 heats) and the layer ratio imbalance (41 heats); when the MgO content of the anti-corrosion layer is lower than the lower limit of this invention, the life drops sharply to 28 heats, proving that 75.0-77.0% is the necessary range; without furnace cleaning treatment, the life is only 19 heats, and corrosion pits appear on the inner wall, indicating that the furnace cleaning process is indispensable. The comparative examples all show thermal shock penetration cracking or severe corrosion, while the examples show slow and uniform wear, indicating a fundamental change in the failure mechanism. This invention, through the synergistic effect of dual-layer functional zoning and gradient sintering, increases the life of high-alumina titanium alloy crucibles by approximately 2.5 times compared to existing single-layer structures.
Claims
1. A method for preparing a long-life magnesium oxide crucible, characterized in that: Includes the following steps: (1) Batching steps: Prepare the first mixed raw material for the thermal shock resistant layer in the upper part of the crucible and the second mixed raw material for the erosion resistant layer in the lower part of the crucible. Add 3-5% water to the first mixed raw material and mix evenly. Do not add water to the second mixed raw material. The mass percentage of MgO in the second mixed raw material is 75.0-77.0%. (2) Compaction molding step: The first and second mixed raw materials are arranged in upper and lower layers and tamped or vibrated to form a crucible blank with a double-layer composite structure; the volume of the thermal shock resistant layer accounts for 15-20% of the total volume of the crucible blank, and the volume of the erosion resistant layer accounts for 80-85% of the total volume of the crucible blank; (3) Sintering step: The graphite core is placed into the prepared crucible blank and sintered. After sintering, the graphite core is removed and the furnace is cleaned with pure iron and pure nickel respectively to obtain a high-life magnesium oxide crucible. The sintering process is as follows: 195-205kW holding time for 118-122 minutes, 295-305kW holding time for 58-62 minutes, 345-355kW holding time for 58-62 minutes, 375-385kW holding time for 58-62 minutes, 395-405kW holding time for 28-32 minutes, 445-455kW holding time for 28-32 minutes, and 495-505kW holding time for 28-32 minutes. The first mixed raw material comprises the following chemical components by mass percentage: MgO: 53.0-54.0%, Al2O3: 34.0-35.0%, SiO2: 7.0-8.0%, TiO2: 1.0-1.5%, CaO: 1.0-1.5%, Fe2O3: 0.4-0.6%, MgCl2: 0.5-1.0%, Na2O·nSiO2: 0.5-1.0%; The second mixed raw material comprises the following chemical components in weight percentage: MgO: 75.0-77.0%, Al2O3: 21.0-23.0%, SiO2: 0.4-0.6%, CaO: 0.5-1.0%, MgCl2: 0.4-0.6%; The sintering process described above includes the thermal shock resistant layer, which contains magnesium oxide, aluminum oxide, titanium oxide, and iron oxide; and the corrosion resistant layer, which contains magnesium aluminum spinel, magnesium oxide, and aluminum oxide. After the graphite core is sintered, a dense sintered shell layer is formed on the inner wall of the lower part of the crucible.
2. The method for preparing a long-life magnesium oxide crucible according to claim 1, characterized in that: The process of furnace cleaning using pure iron is as follows: hold at 95-105kW for 18-22 minutes, hold at 155-165kW for 18-22 minutes, hold at 215-225kW for 8-12 minutes, raise the temperature to 1680-1700℃ at 445-455kW, then adjust the power to 155-165kW and hold for 28-32 minutes, then turn off the power and cool down to 1595-1605℃, then adjust the power to 295-305kW and raise the temperature to 1645-1655℃ for casting.
3. The method for preparing a long-life magnesium oxide crucible according to claim 1, characterized in that: The process of furnace cleaning using pure nickel is as follows: hold at 95-105kW for 18-22 minutes, hold at 155-165kW for 18-22 minutes, hold at 215-225kW for 8-12 minutes, raise the temperature to 1590-1610℃ at 445-455kW, then adjust the power to 155-165kW and hold for 28-32 minutes, then turn off the power and cool down to 1565-1575℃, then adjust the power to 295-305kW and raise the temperature to 1585-1595℃ for casting.
4. The method for preparing a long-life magnesium oxide crucible according to claim 1, characterized in that: The thickness of the dense sintered shell layer is 0.5-1.0 mm.
5. A long-life magnesium oxide crucible, characterized in that: It is prepared by the method of any one of claims 1-4 for preparing a high-life magnesium oxide crucible.
6. An application of the high-life magnesium oxide crucible according to claim 5, characterized in that: For use in vacuum melting furnaces of 500 kg and above, a casting high-temperature alloy containing a high aluminum and titanium content, wherein the high aluminum and titanium content is: aluminum + titanium ≥ 6.0 wt%.
Citation Information
Patent Citations
High-strength magnesium oxide crucible and preparation method thereof
CN112321282A
Furnace lining material used for medium-frequency induction furnace as well as preparation method and use method of furnace lining material
CN104446547A
Steel ladle laying structure and steel ladle using method
CN112264612A